Think to Talk Write Learning Mathematics Tool Hands on Activity - M. Taufik Qurohman (International Journal of Trends in Mathematics Education Research, 2018)
By looking at the learning result of Lecturer of DIII Mechanical Engineering Department of Harapan Bersama seen the lack of understanding of the students understanding the subject matter of Applied Mathematics. The objective of the research is to produce a mathematics learning device with Think Talk Write model based on Hand On Activity to improve the valid ability of troubleshooting, practical, and effective math problem solving. This research is a development research using 4D model that is modified into 3D consists of defining, designing and developing phases. The types of devices developed are: (1) Syllabus; (2) Semester Study Plan; (3) Modules and (4) Worksheets , and (5) Troubleshooting Test. The subject of this research is the D III students of Mechanical Engineering Department. Independent variables of this research are independence and problem-solving skills, while the dependent variable is the result of Troubleshooting test. Conclusions gained (a) Students achieved mastery individually (scores above 80) as well as classical, (b) The ability of troubleshooting of Applied Mathematics in a class that uses Think Talk Write model devices based on Hand On Activity is better than the ability of class math problem solving with conventional method, (c) The existence of influence of independence character and problem solving skill to troubleshooting ability of subject Applied Mathematics equal to 90%.